Can Vitamin D supplementation enhance the effectiveness of exercise-induced weight loss in overweight or obese adults? Evidence from integrated transcriptomic and meta-analysis - Peng, Tianhang; Zhang, Zike; Liang, Wanyuan; Zhang, Jiayi (Frontiers in Nutrition, 2025)
ObjectiveObesity is a major global public health challenge, and Vitamin D deficiency is prevalent among obese individuals. This study aimed to evaluate whether Vitamin D supplementation enhances the effectiveness of exercise-induced weight loss in overweight or obese adults by integrating transcriptomic analysis and meta-analysis.MethodsTranscriptomic data from the GEO and GTEx databases were integrated for differential gene expression analysis, Gene Ontology (GO)/Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment, and Gene Set Enrichment Analysis (GSEA). Currently, clinical transcriptomic data regarding the effect of Vitamin D on exercise intervention outcomes in overweight/obese adults is limited. To address this gap, this study utilized cold-induced skeletal muscle shivering as a surrogate model to explore its potential molecular mechanisms. A meta-analysis of eight randomized controlled trials (RCT) involving 481 participants, was conducted to assess the combined effects of exercise and Vitamin D supplementation on body composition and metabolic parameters, with subgroup analyses by age and exercise type.ResultsTranscriptomic analysis revealed abnormal expression of Vitamin D metabolism-related genes in skeletal muscle of obese individuals, with enrichment in pathways such as lipid digestion and absorption. Post-intervention, Vitamin D response pathways were significantly upregulated. The meta-analysis showed that combined intervention had a significant effect on waist circumference (mean difference [MD] = −1.48, 95% CI: −2.02 to −0.94, p < 0.05). Subgroup analysis indicated that improvements in body weight and Body Mass Index (BMI) were more pronounced among older adults and those undergoing aerobic exercise.ConclusionThis study, through integrated high-throughput transcriptomic analysis and meta-analysis, systematically demonstrates that Vitamin D supplementation may enhance skeletal muscle metabolic responsiveness to exercise in overweight or obese adults. The effect appears especially significant in older populations and within aerobic exercise contexts. These findings suggest that Vitamin D supplementation could serve as a synergistic strategy in exercise-based weight loss programs for targeted populations. Future research should focus on individual Vitamin D status, optimization of exercise modalities, and validation of underlying mechanisms to support personalized and precise interventions.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/.